Integritas Pemilu sebagai Prasyarat Demokrasi: Telaah Konseptual atas Peran KPU, Bawaslu, dan DKPP - Hasna Hasna; Prisma Fatma Sari; Muhammad Indra Adi Satria Wijaya; Reno Mandala Putra; Elviandri Elviandri (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study examines the functions and authorities of the General Elections Commission (KPU), the Election Supervisory Agency (Bawaslu), and the Election Organizers Ethics Council (DKPP) in achieving democratic elections in Indonesia. KPU serves as the primary election organizer, Bawaslu acts as both supervisor and resolver of administrative disputes, and DKPP functions as an ethical institution that safeguards the integrity of election organizers. These three institutions hold strategic positions within the constitutional system, complementing one another through executive, supervisory, and code of ethics enforcement functions. Through institutional synergy, the principles of democracy, justice, and good and clean governance can be realized at every stage of the election.